The defendant and his rights - Albu, Bianca Nicoleta (Eximia, 2023)
Antisocial acts are the natural product resulting from the relationship between individuals, existing and having the possibility that they are framed as inhuman, unethical, which do not depend on any kind of legal settlement. However, they cannot be considered as criminal offences only when the law considers them to be prohibited, punishing them with penalties. Citizens enjoy the rights and freedoms enshrined in the Constitution or other laws, as well as the obligations provided for therein, guaranteeing equality before the law, public authorities, without discrimination. Citizens must exercise their rights and freedoms in good faith so as not to violate the rights and freedoms of others. The conduct of criminal proceedings confers on the offender different qualities but each with different legal meanings, and depending on these procedural qualities, the active subject of the crime will have certain rights and obligations, which he will bear in the procedural activity. According to the current legislation, the criminal investigation body, in order to find out the truth, is obliged, even if the defendant admits the act, to collect evidence in his favor and against him. The defendant is considered by the entire legal literature to be the only main part of the criminal process, which cannot be disputed. At the same time, the central subject of the completion of the procedural activity, through sincere statements, the defendant contributes to the just settlement of the case, the judicial bodies having the possibility to establish the hypostasis in which the deed was committed.